Differential TGFβ pathway targeting by miR-122 in humans and mice affects liver cancer metastasis - Shenyi Yin (Nature Communications, 2016)
MiR-122 levels correlate with metastasis in human liver cancer but not in mouse models. Here the authors show that miR-122 targets TGFßR1 in mice but TGFß1 in humans, that swapping this specificity affects metastasis, and that many other receptor-ligand pairs are differentially targeted by miRNAs across species.